2021
DOI: 10.1523/jneurosci.2494-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Cereblon Regulates the Proteotoxicity of Tau by Tuning the Chaperone Activity of DNAJA1

Abstract: Protein aggregation can induce explicit neurotoxic events that trigger a number of presently untreatable neurodegenerative disorders. Chaperones, on the other hand, play a neuroprotective role because of their ability to unfold and refold abnormal proteins. The progressive nature of neurotoxic events makes it important to discover endogenous factors that affect pathologic and molecular phenotypes of neurodegeneration in animal models. Here, we identified microtubule-associated protein tau, and chaperones Hsp70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Recently, a remarkable effect of HSP70 in promoting memory formation was reported [133]. Specifically, a recent manuscript by Akber (2021) [134] indicates that HSP70 is a key protein used to protect against deleterious effects induced by p-Tau, which enhances the dual effects of LC-NE axons in modulating the amount of these proteins within limbic areas, as evidenced in the present manuscript. The loss of p62 appears to have a significant value for the onset of neurodegeneration.…”
Section: Discussionsupporting
confidence: 59%
“…Recently, a remarkable effect of HSP70 in promoting memory formation was reported [133]. Specifically, a recent manuscript by Akber (2021) [134] indicates that HSP70 is a key protein used to protect against deleterious effects induced by p-Tau, which enhances the dual effects of LC-NE axons in modulating the amount of these proteins within limbic areas, as evidenced in the present manuscript. The loss of p62 appears to have a significant value for the onset of neurodegeneration.…”
Section: Discussionsupporting
confidence: 59%
“…In parallel, another study tested HSP40 effects on the AD-associated protein tau showing that overexpression of DnaJA1 can favor both tau clearance and stabilization dependent on Hsp70 levels in M17 neuroblastoma cells (Abisambra et al, 2012). A recent study reported similar findings, whereby inducing DnaJA1 activity by CRBN (endogenous substrate of cerebelon) downregulation decreased phosphorylation and aggregation of tau, which was detected in vivo and in vitro (Akber et al, 2021). Furthermore, Abisambra et al also demonstrated DnaJA1-induced polyQ clearance, while alpha-synuclein stability was unaffected in a model of Parkinson's disease.…”
Section: Discussionmentioning
confidence: 73%
“…Our findings may therefore help to reconcile these inconsistencies as CB 1 Rs reduce glutamate release (Piomelli, 2003 ) and may also activate BK Ca channels under certain conditions (Stumpff et al, 2005 ; Romano and Lograno, 2006 ; López-Dyck et al, 2017 ). Furthermore, CRBN-KO mice show a resilient phenotype towards stress (Akber et al, 2022 ; Park et al, 2022 ) and the pathological aggregation of Tau, a hallmark of tauopathies as Alzheimer’s disease (Akber et al, 2021 ). Facilitation of CB 1 R signalling also protects against acute and chronic stress, and chronic stress consistently downregulates CB 1 R (Morena et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%